Take me to your leader : perspectives on your first alien encounter - Tyson, Neil deGrasse (Simon Six, 2026)
"'Ever since childhood,' writes Neil deGrasse Tyson, 'I've wanted to be abducted by Aliens.' Take Me to Your Leader is the culmination of a lifetime of fascination, speculation, and the amassing of scientific data about the possibility of Aliens visiting Earth. Drawing on a wealth of depictions from history, literature, pop culture, and film, Tyson applies the universal laws of physics to make the case for what Aliens might look like, act like, how they might travel through the universe to reach us, and what they might think of us upon arrival. Should such an event occur, Tyson further offers useful etiquette tips for your first close encounter. If you've ever wondered why there are so many UFO sightings, or whether Aliens might already be among us, Tyson offers an informed perspective that is both factual and fun. Take Me to Your Leader is a tantalizing exploration of what would be the most mind-blowing experience of your life--the book for anyone who has ever wondered: Are we alone?"-- Provided by publisher.